Professional Learning from Disturbances in Healthcare: Managerialism and Compassion - Katie Willocks; Jem Bendell; Richard Little (International Journal of Management, Knowledge and Learning, 2020)
This study asks what behaviours might convert professional disturbances in maternity wards into opportunities for learning within healthcare and how that process is influenced by models of management and leadership. A framework of Cultural History Activity Theory helped to analyse moments of fractured collaboration in which uncertainty about roles and differences in professional status was a factor. Implications for professional learning are discussed along with the frames that might give coherence and utility to future research. We conclude that any interventions to support professional learning should reflect the broadly compassionate ethos that informs the commitments and activities of healthcare workers.